Legal Analysis of Storing Cutlery From Gold and Silver Perspective of the Syafi'i Opinion - Saefudin Saefudin; Aziz Nurul Iman; Junaedi Junaedi; Barlian Fajri (Al-Jadwa: Jurnal Studi Islam, 2023)
The use of gold and silver in cutlery and containers has become a symbol of social status and wealth in various societies, including in Roman times, Europe, America and the Archipelago. This research is a type of library research, which involves reading, studying and analyzing various relevant literature. keeping containers of gold and silver is haram, and can be understood as a step taken to avoid the potential for excessive use, waste of property, or even the impression of arrogance that can arise from the use of these luxury items. However, al Imrani argued that there was no prohibition against keeping containers or cutlery made of gold. According to him, keeping valuable cutlery, such as those made of gold and silver, is permitted because it has economic value which can assist in the development of one's wealth. In the Ushul Fiqh Science Discipline, the prohibition of the use of storing containers made of gold and silver is carried out using the sadd al-żari'ah approach, namely deciding the path of damage. Imam Ibn al-Qasim outlines his views on the use of vessels involving gold or silver coating. According to him, if a vessel contains a layer of gold or silver and if the vessel is placed at a high temperature so that the gold or silver coating melts or disappears, then the use of such a vessel is considered haram.